Pengembangan Produksi Media Pembelajaran Untuk Meningkatkan Nilai Ekonomi Guru Bagi Mahasiswa PGMI UIN Raden Mas Said Surakarta - Suprapti Suprapti (Universitas Nusantara PGRI Kediri, 2021)
Learning media is a tool that can help the teaching and learning process so that the meaning of the message conveyed becomes clearer and the goals of education or learning can be achieved effectively and efficiently. Learning media serves as a learning resource for students to obtain messages and information provided by the teacher so that learning materials can further shape knowledge for students. But from the teacher's point of view, making learning media is for the needs of teaching in the classroom. In addition, learning media can contribute to improving teacher welfare. So it is necessary to develop the production of learning media that can be of economic value for the general public. This research was conducted using the ADDIE model, which is one of the development models of the Research and Development (R&D) method. The learning media used in the classroom are developed into products of economic value that can be sold to the free market using analysis and tests by experts. The results of the research are validations carried out by learning media experts who assess the feasibility of the media design display showing an 80% assessment percentage. Validation by material experts who assessed the presentation of material in the media showed a percentage of 90%. Tests conducted by students to determine student responses to the media showed a percentage of 95%.